Nuclear Proliferation and Global Security: A Comparative Analysis of State Responses to Iran and North Korea’s Nuclear Programs - Ihedioha , Yagazie E.; Badru , Ronald (Kashere Journal of Politics and International Relations, 2025)
This study provides a comparative analysis of international responses to the nuclear programs of Iran and North Korea within the broader context of global security. The proliferation of nuclear weapons by these states has posed significant challenges to the global non-proliferation regime, triggering varied responses from the international community. While Iran has been subjected to a mix of diplomacy and sanctions, North Korea has faced a more hardline stance dominated by isolation and coercive containment. The problem, however, lies in the inconsistency, selectivity, and limited effectiveness of these responses in achieving long-term denuclearization and regional stability. The study is anchored in the theoretical frameworks of realism and constructivism, which help explain both the strategic motivations of the states involved and the normative expectations of the international system. Methodologically, the research adopts a qualitative comparative case study approach, utilizing secondary data from institutional reports, journal articles, and policy documents. Findings reveal that while diplomacy and institutional engagement have produced partial success in Iran, the case of North Korea highlights the failure of sanctions and isolation in achieving nuclear rollback. The paper concludes that global responses are often shaped more by geopolitical interests than by consistent legal norms, weakening the credibility of the non-proliferation regime. It recommends a recalibrated approach combining credible diplomacy, enhanced institutional oversight, and regional security frameworks to address future proliferation threats. By aligning strategic interests with normative enforcement, the international community can better manage the evolving threats to global security posed by nuclear proliferation.